Corporate Debt Maturity in Developing Countries : Sources of Long- and Short-Termism - Cortina, Juan J.; Didier, Tatiana; Schmukler, Sergio L. (World Bank, Washington, DC, 2017)
This paper documents to what extent firms from developing countries borrow short versus long term, using data on corporate bond and syndicated loan markets. Contrary to claims in the literature based on firm balance sheets, firms from developing countries borrow through bonds and syndicated loans at maturities similar to those obtained by developed country firms. The composition and use of financing matters. Firms from developing countries borrow shorter term in domestic bond markets, but the differences in international issuances (accounting for most of the proceeds) are significantly smaller. Developing country firms borrow longer term in syndicated loan markets, which they partially use for infrastructure projects. However, only large firms from developing countries (similar in size to those from developed ones) issue bonds and syndicated loans. The short-termism in developing countries is partly explained by a lower proportion of firms using these markets, with more firms relying on other shorter-term instruments.